Hungry people and empty lands : an essay on population problems and international tensions - Chandrasekhar, S. (Sripati), 1918-2001 (Routledge library editions. Development, 2011)
First published in 1954, this reissue deals with the problem of international tensions arising from demographic and fertility differences, with special reference to such heavily populated Asian countries as China, Japan and India.